2022
DOI: 10.3390/en15093035
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Measurements for Monitoring CO2 Foam Pilots

Abstract: This study focuses on the use of pressure measurements to monitor the effectiveness of foam as a CO2 mobility control agent in oil-producing reservoirs. When it is applied optimally, foam has excellent potential to improve reservoir sweep efficiency, as well as CO2 utilization and storage, during CO2 Enhanced Oil Recovery (EOR) processes. In this study, we present part of an integrated and novel workflow involving laboratory measurements, reservoir modeling and monitoring. Using the recorded bottom-hole pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, the base case SAG's BHP values were significantly higher than the observed BHP, especially after the fourth SAG cycle. This suggests that the foam generated during the pilot was not as strong as in laboratory studies as also observed in [25]. In addition, the simulated BHP did not match the observed pressure fall-off after the seventh cycle because the model did not capture the effect of nearby production wells on injection BHP.…”
Section: Radial Model: Baseline Wag and Base Case Sagmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the base case SAG's BHP values were significantly higher than the observed BHP, especially after the fourth SAG cycle. This suggests that the foam generated during the pilot was not as strong as in laboratory studies as also observed in [25]. In addition, the simulated BHP did not match the observed pressure fall-off after the seventh cycle because the model did not capture the effect of nearby production wells on injection BHP.…”
Section: Radial Model: Baseline Wag and Base Case Sagmentioning
confidence: 83%
“…As discussed previously, fmmob is the maximum gas mobility reduction that can be achieved with foam. Previous modeling results have shown that this parameter has the most impact on the simulated BHP [25].…”
Section: Foam Model Sensitivity Studymentioning
confidence: 91%
See 1 more Smart Citation